How risky sukuk are: comparative analysis of risks associated with sukuk and conventional bonds - Nanaeva, Zhamal K (2010)
Recent issues of Islamic bonds were “welcomed” with broad criticism, both by Islamic scholars and conventional investors. Presented paper attempts to analyze sukuk-associated risks and problems, and review their competitiveness in the capital market. In doing so, it compares sukuk with its conventional counterparts and conducts empirical analysis of the Value-at-Risk of both instruments in order to present potential sukuk investors with complete picture.